Check & mate - Hazelwood, Ali (New York : Penguin Teens, 2023)
When eighteen-year-old Mallory begrudgingly agrees to return to chess in one last charity tournament, her surprise upset against Nolan Sawyer, the reigning world champ and bad boy of the chess world, sets her on an worldwin adventure as she rediscovers her passion for the game.
Ages 14 years and up.
Keywords: Chess -- Fiction; Interpersonal relations -- Fiction; Family problems -- Fiction; Romance fiction; Novels